1990
DOI: 10.2307/3430691
|View full text |Cite
|
Sign up to set email alerts
|

Upper Respiratory Tract Tumors in Cpb:WU (Wistar Random) Rats

Abstract: A survey is given of upper respiratory tract tumors in Cpb:WU (Wistar random) rats. Data were collected from ten 24-to 30-month toxicity/carcinogenicity studies and from one 12-month study. Nasal tumors may lead to dyspnea, mouth breathing, and nasal discharge. These clinical signs mainly occurred in rats bearing squamous cell carcinomas. The large nasal tumors were often osteolytic, they invaded the subcutis over the premaxilla, resulting in swellings on the back of the nose, and extended into the brain. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Musculoskeletal and respiratory systems of Wistar rats are rarely affected by spontaneous neoplasms (Bomhard et al, 1986;Kroes et al, 1981;Feron et al, 1990;Novilla et al, 1991). In this review, 0.6% of all neoplasms were in these tissues, an incidence lower than the 1.9% of our previous review but comparable to the 0.5% reported in BOR:WISW rats.…”
Section: Discussionsupporting
confidence: 50%
“…Musculoskeletal and respiratory systems of Wistar rats are rarely affected by spontaneous neoplasms (Bomhard et al, 1986;Kroes et al, 1981;Feron et al, 1990;Novilla et al, 1991). In this review, 0.6% of all neoplasms were in these tissues, an incidence lower than the 1.9% of our previous review but comparable to the 0.5% reported in BOR:WISW rats.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, we also observed ten independent clusters of genes encoding products related to the cell cycle, regulation of transcription, RNA processing, protein interactions, metabolic processes, programmed cell death, the endoplasmic reticulum-nucleus signaling pathway, epigenetic modification, cytoskeleton modification and import into the nucleus (data not shown). In the third group (3,252 genes with similar expression in Nlrp3 −/− and wild-type T H 2 cells), we observed only two clusters of genes encoding products related to DNA repair and microtubule-based transport (Supplementary Fig. 4b).…”
Section: A R T I C L E Smentioning
confidence: 93%
“…However, reports suggest that NLRP3 protein is expressed not only in myeloid cells but also in epithelial cells 2,3 or lymphoid cells 4 . Classic activators of NLRP3 have been shown to induce the production of IL-1β by various epithelial cells, such as retinal epithelial cells 2 , or renal tubular cells 3 . In the context of lymphoid cells, expression of NLRP3 has been detected in both mouse CD4 + T cells and human CD4 + T cells 4 .…”
mentioning
confidence: 99%
“…Homburger (1975) reported induction of laryngeal carcinomas in Syrian hamsters exposed to cigarette smoke for up to 24 months. Feron et al (1982Feron et al ( , 1990 reported the induction of a small number of laryngeal carcinomas in rats and hamsters inhaling acetaldehyde or propylene oxide for 24 months. Conversely, there are numerous published reports of chronic inhalation exposures of rodents to irritant compounds such as tobacco smoke (Dalbey et al, 1980), ozone (Boorman et al, 1994), hexachlorocyclopentadiene (National Toxicology Program [NTP], 1994), and molybdenum trioxide (NTP, 1997) in which laryngeal squamous metaplasia was induced but progression to neoplasia was not present, even after lifetime exposure.…”
Section: Resultsmentioning
confidence: 99%